Isotope-targeted glycoproteomics (IsoTaG): a mass-independent platform for intact N- and O-glycopeptide discovery and analysis - Woo, Christina M (Nat Methods, 2015)
Protein glycosylation is a heterogeneous post-translational modification (PTM) that plays an essential role in biological regulation. However, the diversity found in glycoproteins has undermined efforts to describe the intact glycoproteome via mass spectrometry (MS). We present IsoTaG, a mass-independent chemical glycoproteomics platform for characterization of intact, metabolically labeled glycopeptides at the whole-proteome scale. In IsoTaG, metabolic labeling of the glycoproteome is combined with (i) chemical enrichment and isotopic recoding of glycopeptides to select peptides for targeted glycoproteomics using directed MS and (ii) mass-independent assignment of intact glycopeptides. We structurally assigned 32 N-glycopeptides and over 500 intact and fully elaborated O-glycopeptides from 250 proteins across three human cancer cell lines and also discovered unexpected peptide sequence polymorphisms (pSPs). The IsoTaG platform is broadly applicable to the discovery of PTM sites that are amenable to chemical labeling, as well as previously unknown protein isoforms including pSPs.